Contraception and Diabetes Mellitus - Panou, Theodoros; Gouveri, Evanthia; Gerede, Angeliki; Tsikouras, Panagiotis; Papazoglou, Dimitrios; Papanas, Nikolaos (Experimental and Clinical Endocrinology & Diabetes, 2025)
The aim of this narrative review was to discuss data on contraception in diabetes mellitus (DM). Women with DM rarely discuss contraception with their physicians, and healthcare providers offer advice to a very limited number of them. Overall, 1 in 8 women with DM using contraception methods was found to use an ineffective one. A further issue relates to drug-drug interactions between anti-diabetic medications and oral contraceptives. Generally, anti-diabetic agents do not alter the pharmacologic profile of hormonal contraception. However, preliminary results indicate that some novel anti-diabetic agents may even render oral contraceptive methods ineffective. Several implants can be also generally used by women with both DM types. The relationship between oral contraceptives and diabetic complications has not been clarified yet. In general, implants, intra-uterine devices or progestin-only contraceptives are considered safe options for women with DM. However, short-term use of combined hormonal contraception is also feasible for women without severe complications or risk factors.
Keywords: type 1 diabetes mellitus; type 2 diabetes mellitus; contraception; drug-drug interaction; fertility